Antimicrobial resistance in UK neonatal units: neonIN infection surveillance network. Issue 5 (26th October 2017) - Cailes, Benjamin; Kortsalioudaki, Christina; Buttery, Jim; Pattnayak, Santosh; Greenough, Anne; Matthes, Jean; Bedford Russell, Alison; Kennea, Nigel; Heath, Paul T
Abstract : Objective: To define the susceptibilities of the common causative pathogens of neonatal sepsis in the UK. Design: Retrospective analysis of the prospectively collected neonIN infection surveillance network data between 2005 and 2014. Setting: 30 neonatal units in the UK. Patients: Newborns admitted to participating neonatal units who return a positive blood, cerebrospinal fluid or urine culture and are treated with at least 5 days of appropriate antibiotics. Results: 1568 isolates with recorded antimicrobial data were collected including 328 early-onset sepsis (EOS) isolates and 1240 late-onset sepsis (LOS) isolates. The majority of EOS pathogens (>92%) were susceptible to the four empirical commonly used antimicrobial combinations (eg, 93% for benzylpenicillin/gentamicin), while LOS pathogens demonstrated higher levels of resistance (eg, 89% for flucloxacillin/gentamicin). Among infants<1500 g and <32 weeks gestation, an amoxicillin/gentamicin combination demonstrated a trend towards improved coverage of EOS isolates than benzylpenicillin/gentamicin (93% vs 86%, p=0.211). Conclusions: This analysis provides insights into the patterns of antimicrobial resistance among UK neonatal pathogens. These data will inform areas of future research and can be used to update national evidence-based guidelines on antimicrobial usage.